EFFECTS OF WAVE PERIOD ON WAVE TRANSMISSION AND REFLECTION FOR AN ARRAY OF GEOTUBE - TANG, PANG NENG (Universiti Teknologi PETRONAS, 2020)
Geotube were widely used in the world to serve the function as wave attenuator and promote sedimentation for coastal protection and even land reclamation. In Malaysia, Technical Committee is on Research and Development (RDTC) lead by the Forest Research Institute Malaysia (FRIM) was assigned to conduct research and development related to rehabilitation of mangrove forest and protection in areas with high risk of coastal erosion. The successful rate of rehabilitation of mangrove forest along the coastline was low as the big wave action erodes the planting site, therefore, geotubes (soft woven geo-textile sand filled tube) was installed in the study site located at Sungai Haji Dorani, Selangor to mitigate this problem and shows success after few years. In recent years, the study of hydraulic characteristics of geotube breakwater in terms of wave height had been carried out by different researches but studies on the hydraulic performance in terms of wave period yet to be carried out.